2016
DOI: 10.1016/j.jpowsour.2016.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Edge/basal/defect ratios in graphite and their influence on the thermal stability of lithium ion batteries

Abstract: Raw graphite can be processed industrially in large quanta but for the graphite to be useful in lithium ion batteries (LIB's) certain parameters needs to be optimized. Some key parameters are graphite morphology, active surface area, and particle size. These parameters can to some extent be manipulated by surface coatings, milling processes and heat treatment in various atmospheres. Industrial graphite materials have been investigated for use as anode material in LIB's and compared with commercial graphite. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…Along with the adsorption-energy distribution (AED) of the graphite [ 28 , 29 , 30 , 31 ], values of the specific surface areas can be obtained ( Figure 1 a). The adsorption-potential energy of nitrogen has been obtained from the van der Waals force model, with the potential region at approximately 60 K for the basal plane, ~26 and ~44 K for the edge plane, and ~86 and 96 K for the defect site (by k B T where k B = 8.617 × 10 −5 eV K −1 ) [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the adsorption-energy distribution (AED) of the graphite [ 28 , 29 , 30 , 31 ], values of the specific surface areas can be obtained ( Figure 1 a). The adsorption-potential energy of nitrogen has been obtained from the van der Waals force model, with the potential region at approximately 60 K for the basal plane, ~26 and ~44 K for the edge plane, and ~86 and 96 K for the defect site (by k B T where k B = 8.617 × 10 −5 eV K −1 ) [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have also confirmed the cycle life with the pore volume of 1–10 nm in diameter, and the negative linear relationship of the cyclability according to the pore volume was more pronounced than the tendency according to the non-basal site ( Figure 5 b,c). The BJH method assumes that the pores are cylindrical, but since it is also applied to slit-shaped pores, pores of 1–10 nm appearing in graphite can be considered as defective sites, such as steps or surface roughness [ 32 , 33 , 34 ]. The pore distributions of graphite samples are shown in Figure S6 , and it can be shown that the non-basal sites are not perfectly proportional to the pore volume ( Figure S6c ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, FEC may be reduced via two other multi-electron transfer mechanisms that result in the formation of either CO2 2-, F, and . CH2CHOor CO 2 (Fig. 2, left).…”
Section: Solvent Decomposition At the Lithiated Si Surfacementioning
confidence: 99%
“…Lithium-ion batteries (LIBs) are suitable candidates to drive the technology to harvest a higher energy density to power portable devices and EVs. A typical electrochemical cell for this system includes graphitelithium cobalt oxide (LiCoO2) with lithium hexafluorophosphate (LiPF6) and organic solvents as the electrolyte mixture [1,2]. Graphite has replaced lithium metal as the anode electrode material due to the uncontrollable dendritic Li growth and limited Coulombic efficiency (C.E.)…”
Section: Introductionmentioning
confidence: 99%